Bullying, Depression, and Suicidal Ideation Among Adolescents in the Fujian Province of China: A Cross-sectional Study. Issue 5 (February 2016) - Hong, Lingyao; Guo, Lan; Wu, Hong; Li, Pengsheng; Xu, Yan; Gao, Xue; Deng, Jianxiong; Huang, Guoliang; Huang, Jinghui; Lu, Ciyong
Abstract : Abstract: The relationship of bullying with suicidal ideation among adolescents is controversial. Although depression has been related to bullying and suicidal ideation, little is known about the combined impacts of depression and bullying on suicidal ideation. A sample of 20, 509 high school students from Fujian Province were selected randomly by multistage stratified sampling. All participants completed an adolescent health status questionnaire. Three categories of bullying were assessed: perpetration, victimization, and both (victimization and perpetration). The associations of these 3 categories of bullying with depression and their interaction with suicidal ideation were examined in logistic models. After adjustment for potential confounders, all 3 categories of bullying (perpetration, victimization, and both) were related to increased risk of suicidal ideation with odds ratios (ORs) of 1.66 (95% confidence interval [CI] 1.20–2.30), 2.74 (95% CI 2.29–3.29), and 2.83 (95% CI 2.27–3.52), respectively. There was an interaction between depression and bullying ( P  = 0.001). Subgroup analyses showed a stronger association between perpetration and suicidal ideation in students with depression (odds ratio [OR] 2.97; 95% CI 1.44–6.09) than in those without depression (OR 1.65; 95% CI 1.19–2.28). The association between victimization and suicidal ideation was weaker in students with depression (OR 1.49; 95% CI 1.07–2.07) than in those without (OR 2.69; 95% CI 2.24–3.23). The association of both victimization and perpetration with suicidal ideation was weaker in students with depression (OR 2.22, 95% CI 1.43–3.47) than those without (OR 2.78; 95% CI 2.23–3.47). We observed an independent association of bullying with increased risk of suicidal ideation among adolescent students, and this association was affected by depression. Prospective studies should be conducted to confirm these findings.